Evaluation of Prescription Errors in Teaching Hospital - Shrestha, Binaya (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Prescription errors have been frequent problem in health care settings. Due to prescription error patients lose their faith towards healthcare providers. Therefore the study of prescription errors is necessary to promote rational use of medicine. The aim of the study was to assess the prescription errors found in the different wards of our institution. MATERIAL AND METHODS A prospective observational study was conducted from June 2022 to January 2023 in a tertiary care teaching hospital in Kathmandu. Prescriptions of 350 patients admitted to the different wards of the hospital were included in the study after obtain ing ethical clearance from institutional review committee. A convenience sampling technique was used for collection of the data and the primary data were collected from the patient cardex and recorded in pre-designed proforma consisting of information about, diagnosis of disease and ﬁndings related to prescription errors. Data were entered in the MS excel and further analysis was done using IBM Statistical Package for Social Sciences (SPSS) version 21. RESULTS A total of 350 prescriptions belonging to patients admitted to the different wards were analyzed. Prescription errors were detect- ed in 86 prescriptions. Errors of omission were found in 19 prescriptions and 67 prescriptions showed error of commission. Among errors of commission drug interactions were most common. CONCLUSION Nearly one fourth of prescriptions analyzed showed prescription error. Among them most common were errors of commission. Prevalence of drug interactions is signiﬁcant and needs to be monitored more promptly in our institution.